Artificial Intelligence for Customer Service - Jain, Deepak (Indian Journal of Computer Science, 2024)
In recent years, Artificial Intelligence (AI) technologies have been the integration into customer service. The present research paper provides a comprehensive review of AI applications in customer service, highlighting the various techniques, tools, and platforms employed to enhance customer satisfaction and operational efficiency. Additionally, it discusses the challenges associated with implementing AI in customer service and outlines future directions for research and development in this burgeoning field.